Nanocarbon Electronics - Zhou, Changjian; Zhang, Min.; Yang, Cary Y. (Milton : Jenny Stanford Publishing, 2020)
This book presents a comprehensive review of research on applications of carbon nanotubes (CNTs) and graphene to electronic devices. As nanocarbons in general, and CNTs and graphene in particular, are becoming increasingly recognized as the most promising materials for future generations of electronic devices, including transistors, sensors, and interconnects, a knowledge gap still exists between the basic science of nanocarbons and their feasibility for cost-effective product manufacturing. The book highlights some of the issues surrounding this missing link by providing a detailed review of the nanostructure and electronic properties, materials, and device fabrication and of the structure-property-application relationships.
5.5 Graphene FETs in CMOS Circuits -- 5.6 Novel Graphene Transistor Structures -- 5.7 Radio-Frequency Graphene Electronics -- 5.8 Flexible Graphene Electronics -- 5.8.1 Preparation of Flexible Graphene Thin Film -- 5.8.2 Flexible Graphene Transistor -- 5.9 Summary -- 6. Nanocarbons for Flexible Sensing Applications -- 6.1 Introduction and Overview for Flexible Nanocarbon Electronics -- 6.2 Flexible Device Fabrication -- 6.2.1 Flexible Substrate Selection -- 6.2.2 Fabrication Techniques -- 6.2.2.1 Lithography -- 6.2.2.2 Nanocarbon ink preparation -- 6.2.2.3 Nanocarbon printing
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Electronics; Carbon nanotubes; Graphene; TECHNOLOGY / Electronics / General; TECHNOLOGY / Optics; SCIENCE / Electromagnetism